Systematic Literature Review on Software Requirement Engineering in 5.0 Industry: Current Practices and Future Challenges - Pujiharto, Eka Wahyu; Tikasni, Elisa; Lewu, Retzi; Sudirman, San; Utami, Ema (International Journal of Advanced Science Computing and Engineering, 2024)
The advancements in technology within the industrial era 5.0 are swiftly progressing, particularly in software research and development, exerting a profound influence on various facets of software engineering, notably known as requirements engineering. This research undertakes a systematic literature study from 2020 to 2023, focusing on software system requirements engineering publications and exploring diverse methodologies and implementations. Most are journals and proceedings within these years. This SLR identifies, evaluates and interprets the prevailing practices in Requirements Engineering within the domain of 5.0 Industry. Specifically, it sheds light on the basic method used recently, highlighting adopting agile methodologies, model-based engineering, and interdisciplinary collaboration as auspicious trends. Initially, a pool of 137 articles from Scopus discussing software requirements engineering was identified and refined to 53 final articles based on predefined keywords. This result shows that current methodologies and trends are lacking in meeting new difficulties, which was raised as the side effect of 5.0. It implies the importance of a greater emphasis on cybersecurity, agile development processes, interoperability, and the smooth integration of IoT and AI technologies. The needs are the formidable challenges stemming from the intricacies of system architectures, and the absence of standardization looms large, necessitating concerted efforts for resolution. System architecture must be made in a compact form without any bargain while, at the same time, international standards should be proposed to meet the evolution of software requirement engineering. These findings underscore the imperative for innovation, data security, and an integrative approach to navigating the dynamic landscape of Industry 5.0.